The Potential Role of Apigenin in the Enhancement of the Antioxidant Adaptation to Exercise by Bioactive Dietary Compounds - Reuquen-Lopez, P; Flores-Lucero, F; Poblete-Aro, C (SOC CHILENA NUTRICION, BROMATOLOGIA & TOXICOLOGIA, 2023)
Oxidative stress (OS) occurs when the antioxidant defense system is overwhelmed by the predominance of reactive oxygen species (ROS) and pro -oxidant factors. Several diseases such as hypertension, insulin resistance, type 2 diabetes mellitus and neurodegenerative diseases are characterized by chronic OS. Physical exercise constitutes an affordable tool to prevent or ameliorate these conditions. However, during physical activity, acute ROS are produced inducing an activation in peroxisome proliferator activated receptor -Gamma Coactivator-1alpha (PGC-1 alpha), and nuclear factor erythroid-2 related factor 2 (Nrf2), PGC-1 alpha/Nrf2 pathway. This signaling pathway facilitates interaction with antioxidant response elements (ARE), thereby initiating an upregulation in the expression of antioxidant enzymes including superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPX) and mitochondrial biogenesis. In both cases, whether involving healthy animals or individuals engaged in physical exercise, supplementation with antioxidant scavengers leads to a reduction in the expression and activity of PGC-1 alpha, SOD, CAT, and GPX across various tissues, which is not observed with indirect antioxidants. The preventive role of physical exercise against chronic OS is avoided when executed in conjunction with supplementation of scavenger antioxidants. However, similar to exercise, the indirect antioxidant apigenin can activate the PGC1-alpha/Nrf2 signaling pathway. Here, we summarize evidence supporting apigenin as a non -nutritional supplement that could enhance the adaptive effects of exercise, improving the endogenous antioxidant defense. Therefore, apigenin could be an interesting supplement to enhance the endogenous antioxidant adaptation induced by exercise in healthy subjects, but also to improve the effectiveness of exercise to prevent oxidative stress -associated diseases.